The age of peak performance in women and men duathletes – The paradigm of short and long versions in “Powerman Zofingen” - Nikolaidis PT; Villiger E; Ardigò LP; Waśkiewicz Z; Rosemann T; Knechtle B (Dove Medical Press, 2018)
Pantelis T Nikolaidis,1,2 Elias Villiger,3 Luca P Ardigò,4 Zbigniew Waśkiewicz,5 Thomas Rosemann,3 Beat Knechtle3,6 1Exercise Physiology Laboratory, Nikaia, Greece; 2Exercise Testing Laboratory, Hellenic Air Force Academy, Acharnes, Greece; 3Institute of Primary Care, University of Zurich, Zurich, Switzerland; 4Department of Neurosciences, Biomedicine and Movement Sciences, School of Exercise and Sport Science, University of Verona, Verona, Italy; 5Department of Team Sports, Academy of Physical Education, Katowice, Poland; 6Medbase St. Gallen Am Vadianplatz, St. Gallen, Switzerland Purpose: The age of peak performance (APP) has been studied extensively in various endurance and ultra-endurance sports; however, less information exists in regard to duathlon (ie, Run1, Bike, and Run2). The aim of the present study was to assess the APP of duathletes competing either in a short (ie, 10 km Run1, 50 km Bike, and 5 km Run2) or a long distance (ie, 10 km Run1, 150 km Bike, and 30 km Run2) race. Participants and methods: We analyzed 6,671 participants (women, n=1,037, age 36.6±9.1 years; men, n=5,634, 40.0±10.0 years) in “Powerman Zofingen” from 2003 to 2017. Results: Considering the finishers in 5-year age groups, in the short distance, a small main effect of sex on race time was observed (p<0.001, η2 =0.052) with men (171.7±20.9 min) being faster than women (186.0±21.5 min) by –7.7%. A small main effect of age group on race was shown (p<0.001, η2 =0.049) with 20–24 years being the fastest and 70–74 years the slowest. No sex × age group interaction was found (p=0.314, η2 =0.003). In the long distance, a small main effect of sex on race time was observed (p<0.001, η2 =0.021) with men (502.8±56.8 min) being faster than women (544.3±62.8 min) by –7.6%. A large main effect of age group on race time was shown (p<0.001, η2 =0.138) with age group 25–29 years the fastest and age group 70–74 years the slowest. A small sex × age group interaction on race time was found (p<0.001, η2 =0.013) with sex difference ranging from –22.4% (15–19 age group) to –6.6% (30–34 age group). Conclusion: Based on these findings, it was concluded an older APP in the long than in the short distance was seen in “Powerman Zofingen.” This indicates that APP in duathlon follows a similar trend as in endurance and ultra-endurance running and triathlon, ie, the longer the distance, the older the APP. Keywords: aging, cycling, master athletes, running, ultra-endurance